2008
DOI: 10.1021/la800331a
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Domains and Membrane Permeability in Phosphatidylcholine−Phosphatidic Acid Rigid Vesicles As a Function of pH and Lipid Chain Mismatch

Abstract: Heterogeneous lipid membranes tuned by pH were evaluated at 37 degrees C in the form of PEGylated vesicles composed of lipid pairs with dipalmitoyl ( n = 16) and distearoyl ( n = 18) chain lengths. One lipid type was chosen to have the titratable moiety phosphatidic acid on its headgroup, and the other lipid type was chosen to have a phosphatidylcholine headgroup. The effect of pH on the formation of lipid heterogeneities and on membrane permeability was studied on vesicles composed of lipid pairs with matchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 38 publications
(57 reference statements)
4
61
0
Order By: Relevance
“…Third, ligand unmasking by acidic pH-induced membrane reorganization has been introduced as a reversible ligand-masking strategy. Sofou and coworkers developed a new platform for pH-triggered liposomal drug delivery [287, 288]. The rationale for their design involves the increased permeability at the boundaries between lipid domains [289].…”
Section: Tumor Stimuli-triggered Peg Releasementioning
confidence: 99%
See 2 more Smart Citations
“…Third, ligand unmasking by acidic pH-induced membrane reorganization has been introduced as a reversible ligand-masking strategy. Sofou and coworkers developed a new platform for pH-triggered liposomal drug delivery [287, 288]. The rationale for their design involves the increased permeability at the boundaries between lipid domains [289].…”
Section: Tumor Stimuli-triggered Peg Releasementioning
confidence: 99%
“…The rationale for their design involves the increased permeability at the boundaries between lipid domains [289]. Using lipid pairs of phosphatidic acid as a titrable headgroup and phosphatidylcholine as the colipid headgroup with mismatched hydrophobic chain lengths (dipalmitoyl and distearoyl) they demonstrated that formation of heterogeneous domains in PEGylated liposomes containing 5% of cholesterol allowed faster pH-dependent content release than liposomes with matched chains [288]. They showed a pH-dependent membrane transition due to the protonation of phosphatidylserine at lower pH in cholesterol-rich membranes, with protonation favoring their homologous interaction, leading to the formation of DSPS (1,2-distearoyl-sn-glycero-3[phosphor-L-serine]) lipid domains.…”
Section: Tumor Stimuli-triggered Peg Releasementioning
confidence: 99%
See 1 more Smart Citation
“…The addition of folate-PEG 3350 -CHEMS made the lipid membranes more heterogeneous due to the poor lipid packing, and thus increased membrane permeability. 45 Pharmacokinetic tests in vivo echoed the results of the drug release in vitro. Only when the drug release is slower than the liposome clearance will the liposome control the drug pharmacokinetics and bio-distribution and express the EPR effect for passive targeting.…”
mentioning
confidence: 99%
“…Additionally, in the slightly acidic tumor interstitium (7.4 > pH > 6.0) [14,15] a pHresponsive mechanism on the liposome membrane results in release of these chelated forms of encapsulated radioactivity [16].…”
Section: Introductionmentioning
confidence: 99%